A randomized trial to reduce the prevalence of depression and self-harm behavior in older primary care patients - Almeida, O.; Pirkis, J.; Kerse, N.; Sim, M.; Flicker, L.; Snowdon, J.; Draper, B.; Byrne, G.; Goldney, R.; Lautenschlager, N.; Stocks, N.; Alfonso, Helman; et al. (2012)
PURPOSE We wanted to determine whether an educational intervention targeting general practitioners reduces the 2-year prevalence of depression and self-harm behavior among their older patients. METHODS Our study was a cluster randomized controlled trial conducted between July 2005 and June 2008. We recruited 373 Australian general practitioners and 21,762 of their patients aged 60 years or older. The intervention consisted of a practice audit with personalized automated audit feedback, printed educational material, and 6 monthly educational newsletters delivered over a period of 2 years. Control physicians completed a practice audit but did not receive individualized feedback. They also received 6 monthly newsletters describing the progress of the study, but they were not offered access to the educational material about screening, diagnosis and management of depression, and suicide behavior in later life. The primary outcome was a composite measure of clinically significant depression (Patient Health Questionnaire score =10) or self-harm behavior (suicide thoughts or attempt during the previous 12 months). Information about the outcomes of interest was collected at the baseline assessment and again after 12 and 24 months. We used logistic regression models to estimate the effect of the intervention in a complete case analysis and intention-to-treat analysis by imputed chain equations (primary analysis). RESULTS Older adults treated by general practitioners assigned to the intervention experienced a 10% (95% CI, 3%-17%) reduction in the odds of depression or self-harm behavior during follow-up compared with older adults treated by control physicians. Post hoc analyses showed that the relative effect of the intervention on depression was not significant (OR = 0.93; 95% CI, 0.83-1.03), but its impact on self-harm behavior over 24 months was (OR = 0.80; 95% CI, 0.68-0.94). The beneficial effect of the intervention was primarily due to the relative reduction of self-harm behavior among older adults who did not report symptoms at baseline. The intervention had no obvious effect in reducing the 24-month prevalence of depression or self-harm behavior in older adults who had symptoms at baseline. CONCLUSIONS Practice audit and targeted education of general practitioners reduced the 2-year prevalence of depression and self-harm behavior by 10% compared with control physicians. The intervention had no effect on recovery from depression or self-harm behavior, but it prevented the onset of new cases of self-harm behavior during follow-up. Replication of these results is required before we can confidently recommend the roll-out of such a program into normal clinical practice.